Obstacle avoidance and smooth trajectory control: neural areas highlighted during improved locomotor performance - Billington, Jaclyn; Wilkie, Richard M.; Wann, John P. (Frontiers in Behavioral Neuroscience, 2013)
Visual control of locomotion typically involves both detection of current egomotion as well as anticipation of impending changes in trajectory. To determine if there are distinct neural systems involved in these aspects of steering control we used a slalom paradigm, which required participants to steer around objects in a computer simulated environment using a joystick. In some trials the whole slalom layout was visible (steering ‘preview’ trials) so planning of the trajectory around future waypoints was possible, whereas in other trials the slalom course was only revealed one object at a time (steering ‘near’ trials) so that future planning was restricted. In order to control for any differences in the motor requirements and visual properties between ‘preview’ and ‘near’ trials, we also interleaved control trials which replayed a participants’ previous steering trials, with the task being to mimic the observed steering. Behavioral and fMRI results confirmed previous findings of superior parietal lobe (SPL) recruitment during steering trials, with a more extensive parietal and sensorimotor network during steering ‘preview’ compared to steer ‘near’ trials. Correlational analysis of fMRI data with respect to individual behavioral performance revealed that there was increased activation in the SPL in participants who exhibited smoother steering performance. These findings indicate that there is a role for the SPL in spatial encoding and updating of future targets or obstacles during forward locomotion, which also provides a potential neural underpinning to explain improved steering performance on an individual basis.